Serum cytokines levels in patients with myocardial infarction with non-obstructive and obstructive coronary arteries - D. A. Vorobyova; I. V. Kologrivova; T. E. Suslova; V. V. Ryabov (Российский кардиологический журнал, 2022)
Aim. To compare the concentrations of proinflammatory and anti-inflammatory cytokines in patients with myocardial infarction with non-obstructive (MINOCA) and obstructive coronary arteries (MIOCA) in the early postinfarction period and after 1-year follow-up.Material and methods. The study included 40 patients with myocardial infarction (experimental group, 19 patients; control group, 21 patients). Three (15,7%) patients with diagnosed acute myocarditis were excluded from the final analysis. Blood samples were taken upon admission, on the 2nd, 4th and 7th days from hospitalization, and also after 1-year follow-up. Twenty-three parameters were analyzed using multiplex analysis and the Multiplex Instrument FLEXMAP 3D system (Luminex Corporation), as well as the MILLIPLEX map Human Cytokine/ Chemokine Panel II.Results. According to multiplex analysis of blood serum of the studied groups, a comparable increase in proinflammatory cytokines CCL-15, CCL-26, CCL-27 in the early postinfarction period and after 1-year follow-up, as well as antiinflammatory and regenerative cytokines CXCL-12, TPO in the early postinfarction period and after 1-year follow-up. In patients with MINOCA, higher concentrations of the following proinflammatory cytokines were determined: IL-16 upon admission (p=0,03), IL-20 on days 2 and 4 of the early postinfarction period (p=0,005 and p = 0.03), as well as CCL-15 on days 4 and 7 (p=0,05 and p=0,02). After 1-year follow-up, among the proinflammatory cytokines, a greater increase in CCL-21 (p=0,02) was noted in the patients of experimental group. Also, in patients with MINOCA, a greater increase in TPO was determined upon admission and on the 2nd day (p=0,02 and p=0,02), SCF — on the 7th day and after 1-year follow-up (p=0,04 and p=0,04), and LIF on the 4th day of early postinfarction period (p=0,007). In contrast, MIOCA patients showed a greater increase in CXCL-12 levels upon admission (p=0,04). At the same time, patients with MINOCA showed a higher level of C-reactive protein on the 1st day, as well as a higher relative monocyte count after 1-year follow-up.Conclusion. Despite a comparable increase in the cytokines CCL-8, CCL-13, CCL26, CCL-27 in patients of both groups, in patients with MINOCA there was a greater increase in proinflammatory cytokines IL-16, IL-20, CCL-15, CCL-21, and also CXCL-12, LIF, TPO, SCF, which have anti-inflammatory and regenerative activity. After 1 year follow-up, MINOCA patients showed a significant increase in CCL-21 and SCF, with a comparable increase in other proinflammatory cytokines in patients of both groups. A greater increase in proinflammatory cytokines in patients with MINOCA may indicate a more aggressive atherosclerosis course and lead to plaque destabilization followed by ischemic event.